A CRITICAL APPRAISAL OF THE PRINCIPLES RELATING TO MISTAKE AND MISREPRESENTATION AS FACTORS AFFECTING CONSENSUS IN CONTRACTUAL AGREEMENTS IN THE NAMIBIAN CONTEXT: DISCUSSION THROUGH THE USE OF EXAMPLES - Awarab, Marvin (Obiter, 2023)
This article suggests that when those engaging in commercial undertakings have a proper understanding of the principles of the law of contract, particularly, the law pertaining to consensus, they will limit the risks of engaging in conduct that will cause them financial loss. The definitions of mistake and misrepresentation (being factors affecting consensus) need to be amplified to avoid existing confusion between the two terms. Misrepresentation and mistake may lead to different respective outcomes and possible remedies, thus necessitating a proper distinction between the two terms. In this light, the article explores and proposes similarities and differences between mistake and misrepresentation. The article further emphasises the fact that misrepresentation involves some form of incorrect representation of facts, whereas in the case of mistake, there is essentially no incorrect representation. Mistake can be said to involve misapprehension of given information, although such information may not be incorrect. It is submitted that the courts should go further than merely looking at the black-and-white before them; they must also pay attention to the conduct of the parties, the intention of the parties and the resulting consequences.